Impact of Nutritional Interventions on Alzheimer's Disease Progression: A Comprehensive Review of Dietary Patterns, Mechanisms, and Clinical Outcomes - Octavia, Indradewi (International Journal on Health and Medical Sciences, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline and memory loss, with increasing prevalence worldwide. Recent research has explored the impact of nutritional interventions on AD progression, aiming to identify effective dietary strategies for prevention and management. This research reviews current evidence on various dietary patterns, including the Mediterranean, MIND, and ketogenic diets, and their effects on cognitive function and AD biomarkers. Advances in understanding the mechanisms through which diet influences AD pathology have highlighted the potential for specific nutrients to modulate neuroinflammation, oxidative stress, and amyloid plaque formation. Despite promising findings, challenges such as long-term diet adherence, variability in individual responses, and ethical considerations in human trials persist. The potential benefits of integrating nutritional strategies into AD treatment plans are substantial, offering a complementary approach to pharmacological therapies and contributing to improved patient outcomes and public health. Addressing these challenges through personalized nutrition and continued research could enhance the effectiveness of dietary interventions and provide a pathway toward more effective prevention and management of Alzheimer’s disease.